PENGARUH MODEL DIRECT INSTRUCTION BERBASIS PERMAINAN TERHADAP KETERAMPILAN DRIBBLING SEPAKBOLA SISWA KELAS VII SMP NEGERI 2 KOTA BARU - Surya Sahri Mahendra Simamora; Evi Susianti; Dikdik Fauzi Dermawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the Effect of Game-Based Direct InstructionModel on Soccer Dribbling Skills of Class VII Students of SMP Negeri 2 Kota Baru.This study uses quantitative descriptive. The data collection technique uses theTest and Measurement of Sports Education and the population in this study were462 students with a sample size of 42 students, while the sampling technique usedwas simple random sampling. Data analysis using paired t sample statistics withSPSS Version 25. The mean value obtained was -14.595, which indicates that theposttest value is higher than the pretest value. The standard deviation value is6.537, and the standard error is 1.009. So this gives an idea that both variableshave an effect, so Ho is rejected and Ha is accepted. It can be concluded Basedon the results of the study and data analysis, it can be concluded that there is asignificant influence of the Game-Based Direct Instruction Model on SoccerDribbling Skills. The results obtained on the pretest score have an average of16.79 with a standard deviation of 3.77, while the minimum pretest score is at 10and the maximum score is 25. While the posttest score with the results is aminimum of 21 points, a maximum score of 40 points, an average of 31.38, astandard deviation of 4.83 and a variance of 23.412. The t value of -14.469 atdegrees of freedom (df) 41 indicates a very significant increase statistically afterthe intervention was carried out. So the results show that there is a significantdifference. Thus the hypothesis (Ha) is accepted and (Ho) is rejected. Acceptedmeans that it provides a significant influence between the Game-Based DirectInstruction Model on Football Dribbling Skills.